INTERNET OF THINGS OF ELECTRONIC SEAL BASE ON GPRS SHORT MESSAGE SERVICE AND THINGSPEAK - Irawati Dewi Syahwir; Agus Samsi; Vera Firmansyah; Prasetyo Wibowo Yunanto; Renanda Maheswara; Navieda Putri Anggraeni (Program Studi Fisika Universitas Negeri Jakarta, 2019)
The field of metrology is mainly legal metrology; seals are closely related to the guarantee or validity of a measuring instrument. Seals are designed so that it is not easy for other parties to open the seal. Seal damage must be identified as soon as possible. The application of the Internet of Things (IoT) is needed in the process of sending data in real-time. IoT technology can be applied to electronic seals to know and record the condition of the measuring device. Broken seals caused by irresponsible parties can cause losses to consumers and owners of measuring instruments. Electronic seals are expected to be able to detect seal damage caused by abuse of authority or fraud. The broken seal will send data to the server as well as SMS (Short Message Service) to the related party. Electronic seals can send damage data via SMS within 20 seconds with a success rate of 92% and sending data through the ThingSpeak web server within 40 seconds with a success rate of 82%.